Application of Copula function in financial risk analysis. (July 2019) - Zhang, Xiwen; Jiang, Hui
Abstract: Copula function is a class of functions that use marginal probability density function to obtain joint distribution. It is used to model multivariate joint distribution and is suitable to apply in the study of finance risk analysis. The purpose of this study is to improve the ability of China's financial industry to resist risks. In this study, firstly, Copula function is introduced into financial risk analysis, and then the research background, significance, research status and theoretical basis of Copula function and financial risk are introduced. Secondly, the time-varying Copula function fitting and the time-varying Copula model fitting of the financial industry and the Internet financial industry are carried out. The results show that there is both upper tail correlation and lower tail correlation between the two indexes, and the correlation between the upper tail and the lower tail is high. Therefore, the results of this research are feasible and have certain practical significance.